Forest Energy in India: The State of the Art - Kaul, R. N.; Gurumurti, K. (Indian Forester, 1981)
Paper reviews the pattern of energy use in rural India and points out that by 1990 fuelwood production will fall short of the requirements by 100 million m3. The importance of biomass in mitigating the energy crisis is outlined. The fuelwood concepts viz.,decentralized fuelwood system-social forestry and commercial fuelwood farming system and their feasibility in meeting the energy requirements have been discussed in detail. Research and developmental efforts in augmenting and utilisation of biomass resource at the national level have been elaborated.